Prototipo de detección de personas autorizadas para encender un vehículo aplicando técnicas de visión artificial en dispositivos móviles android. - Campos Paredes, Jinsop Alexix (2015)
The following degree work is about creating a mobile Android application in order to authorize and detect access to a particular vehicle through facial recognition, for which it uses and manages an electronic device based on a hardware and software platform Arduino (spanish word the name of a program), which will also be installed in the car. For its realization it has been necessary to address the right concepts to mobile apps, android operating system, wireless connection, Bluetooth, artificial machine vision, security, electronic and methodologies for developing mobile applications. The methodology used to develop this application is Mobile-D, this is a methodology for obtaining very fast cycles of development in very small devices, it is also based on known methodologies but they are strictly enforced as extreme programming, Crystal Methodologies and Rational Unified Process. The following methods were used: scientific method, deductive method, and also techniques such as direct observation and literature review, everything encompassed to a good development process. Each of the phases that were carried out within this project has allowed us to obtained the results needed in order to meet each of the objectives and obtain a mobile application to detect and recognize faces as a possible safety improvement from existing security alarms found in cars. For its development and construction it has been integrated software technologies such as Android, Java, C++, OpenCV Android, Android NDK; as well as Android and Arduino phones, getting good results in performance from the prototype built.